Solve using quadratic formula : 4x^2 + 4ax + ( a^2 + b^2 )

Given equation:

4x² +4bx -(a² -b²) = 0
4x² +4bx -a² + b² =0

On factorising we get,
(2x)² + 2.(2x).b + b² -a² =0
(2x + b)² -a² = 0
using the identity a²-b² = (a -b)(a + b)
{2x + b -a}{2x + b +a} =0

We get
x = (a – b)/2 , – (a + b)/2

Was this answer helpful?

 
   

2 (8)

(8)
(1)

Choose An Option That Best Describes Your Problem

Thank you. Your Feedback will Help us Serve you better.

Leave a Comment

Your Mobile number and Email id will not be published. Required fields are marked *

*

*

BOOK

Free Class

Ask
Question